Pengaruh implementasi knowledge management terhadap kinerja karyawan guna pencapaian keunggulan bersaing pada PTPN III Medan - Wina Laila; Bagus Handoko; Ezzah Nahrisah (Forum Kerjasama Pendidikan Tinggi, 2021)
This research is motivated by knowledge management that is notoptimal for each individual or organization, namely on employee performancewhere there are some employees who have not implemented knowledge management at PTPN III Medan, such as a lack of knowledge to manage information in the organization, so that employees in sharing knowledge between employees is not optimal. This study aims to determine whether knowledge management has an effect on competitive advantage. To find out whether knowledge management and competitive advantage partially affect employee performance, to find out whether knowledge management affects employee performance through competitive advantage. The total population in this study was 685 people and 103 were sampled by taking 15% of the total population. The analysis technique used is path analysis. The results showed that knowledge management had an effect on competitive advantage, knowledge management had a significant effect on employee performance, competitive advantage had no effect on employee performance, knowledge management had no effect on employee performance through competitive advantage.